Three new species of Oxyethira Eaton, 1873 (Trichoptera: Hydroptilidae) from New Caledonia - Cavalcante, Bruna Maria Silva; Johanson, Kjell Arne (European Journal of Taxonomy, 2022)
Oxyethira Eaton, 1873 is one of the most diverse genera of Hydroptilidae, comprising over 240 species distributed in all biogeographical regions. Here three new species of Oxyethira (Trichoglene) Neboiss, 1977 are described and illustrated from male specimens collected in New Caledonia: O. (Trichoglene) hamus sp. nov., recognized by the hook-shaped apex of the long inferior appendages in lateral view and by the posterior margin of segment IX with a trilobed appearance in ventral view; O. (Trichoglene) rectangulata sp. nov., recognized by the rectangular shape of the inferior appendages, which are totally fused and with two pairs of small setae on the inner face; and O. (Trichoglene) spiralis sp. nov., recognized by the strongly curvilinear shape of the subgenital process in dorsal and lateral views and by the long process spiralling around the ejaculatory duct at the phallus apex.